Cesarean scar ectopic with ruptured corpus luteal cyst: a rare case report - Yadav, Shikha; Mukherjee, Shubhra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Incidence of caesarean scar pregnancy (CSP) is increasing because of a rising number of caesarean sections. Prompt diagnosis of the condition is required to reduce associated morbidity. A high index of suspicion is required for women with a suggestive history of CSP. Ultrasound scan is the diagnostic tool of choice. Management options include medical, surgical and interventional radiology. Appropriate patient selection is important for optimal results. Major haemorrhage and hysterectomy are the main risks associated with CSP. Therefore, adequate counselling and availability of surgical expertise and blood transfusion should be part of a comprehensive management strategy. We are reporting a rare case of G3P2L1 with previous two lower caesarean deliveries diagnosed with caesarean scar ectopic based on clinical and ultrasound finding came with acute pain in abdomen with haemodynamically unstable with intraoperative finding s/o unruptured c scar pregnancy along with ruptured corpus luteal cyst leading to severe intra-abdominal bleeding. C-scar ectopic and corpus luteal cyst confirmed on histopathology.